Meaning-Making of Occupational Safety and Health Communication among Female Analysts: A Symbolic Interactionism and Feminist Identity Perspective - Silvi Mayyandes; Rita Destiwati (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Occupational Safety and Health (OSH) communication in workplace settings extends beyond the transmission of safety instructions to include how workers interpret and internalize safety messages through lived experience and social interaction. This study explores how female analysts at PT Sucofindo construct meaning from OSH communication in laboratory work environments. A qualitative phenomenological design within an interpretive constructivist paradigm was employed. Data were collected through in-depth interviews, non-participant observation, and documentation involving six female analysts and one QHSE coordinator in Indonesia. Data were analyzed using Moustakas’ phenomenological procedure and cross-case synthesis. The findings show that OSH communication is delivered through safety talks, briefings, toolbox meetings, training, supervisory instructions, QHSE communication, and peer reminders. These messages are interpreted as self-protection, professional responsibility, rule compliance, risk control, collective responsibility, and long-term health awareness. Meaning-making is shaped by workplace experiences such as chemical exposure, heat incidents, and near misses, supported by ongoing social interaction. The study demonstrates that OSH communication is an interpretive meaning-making process rather than mere information transfer. Symbolic Interactionism explains meaning construction through symbols and experience, while Feminist Identity Theory highlights gendered professional identity as a secondary interpretive layer. This study extends OSH communication research by reconceptualizing safety communication as meaning-making, shifting from transmission-based to situated interpretation within workplace interaction and identity. Practically, OSH communication becomes more effective when linked to laboratory hazards such as chemical exposure, furnace heat, and gas vapor risks, reinforced by peer reminders, and supported by near-miss-based learning.